Les ressources scientifiques de l'Occident au service de la modernisation de l'armée ottomane (fin XIXe -début XXe siècle) - Odile Moreau (Revue des Mondes Musulmans et de la Méditerranée)
In the 19th century, the recourse to Western scientific resources appears as a major goal of the Ottoman power. To realize its projects, Istanbul invited foreign military instructors and military missions. The first « Europeanized schools » which opened in the Ottoman Empire were military ones created in reaction to the defeats suffered by the Ottomans. In the first part of the 19th century, the Tanzîmâtgave an important impulsion towards learning modern sciences in the military schools. This kind of education changed the world of the educated officers who played a specific role in Ottoman society.